al-Kalam Ghairu al-Mubasyir fi Surah al-Anbiya’ - Ahmad Riza Firdaus (Jurnal Internasional Pendidikan Bahasa Arab, 2019)
Declarative sentences, in addition to being used to convey news, are also functioned to ask questions; Interrogative sentences are not only used for asking questions but also for requests or orders. Meanwhile, the command sentence can only be used conventionally, and cannot be used unconventionally. If the three sentences are used conventionally, the speech is called a direct speech act, whereas if it is used unconventionally, it is called an indirect speech act. The use of indirect sentences has a purpose, among others, in order to maintain politeness. An order that is told by using a news sentence or question sentence will be perceived by the interlocutor as lighter, even for the interlocutor the command to himself is not felt as an order. In the Alquran there are many sentences that are used unconventionally, which shows that the Alquran is a holy book that upholds the politeness of language. One of them is surah al-Anbiya’. In the surah al-Anbiya’, several verses which are indirect speech are found. In the surah al-Anbiya’ the forms of indirect speech are as follows; Four declarative utterances with imperative meanings are in verses 39, 41, 45, and 47. Seventeen interrogative utterances have declarative meaning in verses 3, 6, 10, 21, 24, 30, 34, 36, 42, 43, 44, 50, 52, 55, 59, 66, and 67. Three meaningful interrogative speeches are found in verses 38, 80, and 108.